Portfolio Behaviour of Commercial Banks under Risk Aversion, The Expected Utility Approach: Evidence from Jordan - Al-Tarawneh, Alaaeddin; Khataybeh, Mohmmad (International Journal of Economics and Financial Issues, 2015)
This paper attempts to explain the banking performance in Jordan to draw out the implications of related theories and evidence for policy makers. Accordingly, they can influence the banking industry, which, in turn, impacts the economy overall. We investigate the portfolio behaviour of Jordanian banks. The model used is based on the portfolio choice theory, originated by Hicks (1935) and developed by Markowitz (1952) and Tobin (1958). Several nested models are developed to test the theoretical restrictions, including symmetry and homogeneity of the interest rate matrix. The empirical results, in general, clearly do not provide any support for interest rates which are important in determining the general composition of the portfolio holdings of Jordanian banks. The results show, however, that availability of funds is more important in determining the structure of these portfolios. Keywords: Portfolio; Banking; Risk aversion; Finance; Expected utility approach JEL Classifications: C51; G11; G17; G21